The use of corticosteroid eye drops in patients post cataract surgey - Ana Claudia; Rusanti, Putri Alivia; Sipangkar, Agnes Imelda; Anugrahsari, Santi (Universitas Kristen Krida Wacana, 2024)
The use of corticosteroid eye drops is one of the post-cataract surgery treatments aimed at reducing inflammation and preventing complications. This literature aims to review the effectiveness and safety of topical corticosteroid use in patients after cataract surgery. Reviewing several recent studies on this topic, this literature finds that topical corticosteroids effectively reduce inflammation and speed up post-operative healing. However, there are risks of side effects, such as increased intraocular pressure (IOP), that need to be considered. The literature also discusses comparisons between corticosteroids and non-steroidal anti-inflammatory drugs (NSAIDs), showing that while NSAIDs are also effective, corticosteroids provide better results in controlling inflammation. In conclusion, corticosteroid eye drops are recommended as the standard treatment after cataract surgery with close monitoring of IOP.